TaWRKY10 transcription factor is a novel jasmonic acid signalling regulator involved in immunity against Septoria tritici blotch disease in wheat. (25th May 2021) - Campanaro, Alberto; Srivastava, Anjil K.; Zhang, Cunjin; Lee, Jack; Millyard, Linda; Gatehouse, Angharad M. R.; Byrne, Ed; Sadanandom, Ari
Abstract : Septoria tritici blotch (STB), caused by the fungus Zymoseptoria tritici, is currently the main threat to worldwide wheat production in temperate climates. Understanding the genetic mechanisms that underpin the Z . tritici– wheat interaction will be crucial for generating new control strategies against STB. Plant hormones are essential regulators of growth and immunity. In particular, jasmonic acid (JA) plays a central role in defence against necrotrophic plant pathogens, but its role in mediating immunity against Z . tritici is largely unknown. Here we identify the transcription factor TaWRKY10 that is taxonomically restricted to the grass subfamily Pooideae as a novel regulator of JA responses in wheat. We demonstrate by using virus‐induced gene silencing that silencing TaWRKY10 leads to increased resistance against Z . tritici with an earlier onset of necrotic symptoms, but with reduced pathogen sporulation. Wheat plants silenced for TaWRKY10 show an up‐regulated JA response. Transcriptional profiling of TaWRKY10 knock‐down plants indicates that it is a negative regulator of the JA receptor TaCOI1 gene expression. Our data indicate that TaWRKY10 down‐regulates JA responses, contributing to the susceptibility of wheat to Z . tritici . We postulate that manipulating TaWRKY10 may provide a strategy to boost STB resistance in wheat. Abstract : TaWRKY10 plays a major role in suppressing immune responses against Zymoseptoria tritici in wheat. We reveal that this immunosuppression is accomplished by down‐regulating jasmonic acid signalling in wheat.